Fuzzy Autoregressive Time Series Model Based on Symmetry Triangular Fuzzy Numbers - Riswan Efendi (Tanjung Malim, 2021)
Fuzzy Autoregressive Time Series Model Based on Symmetry Triangular Fuzzy Numbers by Riswan Efendi